Targeting c-kit inhibits gefitinib resistant NSCLC cell growth and invasion through attenuations of stemness, EMT and acquired resistance - Zhou, Yueling (Am J Cancer Res, 2020)
EGFR tyrosine kinase inhibitors (TKIs) are the first-line drugs for NSCLC. But, the acquired resistance limited their efficacy, so that the patients deteriorate eventually. Therefore, it is necessary to clarify the mechanism of the acquired resistance and overcome it for effective NSCLC therapy. In this experimental study, a stable gefitinib resistant lung adenocarcinoma cell line (PC9/GR) infected with shRNA-c-kit-homo-1386 were established; c-kit siRNA and c-kit inhibitors were used to block c-kit signaling; the acquired resistance of PC9/GR cells and the effects of c-kit siRNA and c-kit inhibitors on the growth and invasion of PC9/GR cells were investigated with CCK-8 assay, colony formation and cell invasion assays in vitro; the tumor growth inhibition effects of c-kit inhibitors on PC9/GR cell generated tumors were tested in vivo; the mechanisms involved in the acquired resistance reverse, growth and invasion inhibition effects of c-kit siRNA and c-kit inhibitors on PC9/GR cells were evaluated with qRT-PCR, Western blot and immunohistochemistry staining. The proliferation, colony formation, and invasion of PC9/GR cells were decreased by c-kit siRNA and inhibitors in vitro significantly; c-kit inhibitors suppressed the tumor growth of PC9/GR cell generated tumors in vivo. In the stable shRNA-c-kit transfected PC9/GR cells, the protein expressions of c-kit signaling and stemness phenotype related proteins, including ALDH1A1, Oct4, Sox2 and ABCG2 were decreased, and EMT phenotype related protein expressions including vimentin, N-cadherin, and Slug, were downregulated and with upregulation of E-cadherin; c-kit inhibitors reduced stemness phenotype related protein expressions, downregulated EMT phenotype related protein expressions including vimentin, N-cadherin, and Slug, with upregulation of E-cadherin, and the stemness related protein expressions of c-kit, ALDH1A1, ABCG2 and EMT-related proteins of vimentin and slug were decreased in the imatinib treated tumor tissues. The findings of this study indicated that c-kit signaling mediated the acquired gefitinib resistance, cell growth, invasion, stemness and EMT phenotype of PC9/GR cells. Targeting c-kit signaling with c-kit siRNA and small molecule c-kit inhibitors might overcome the acquired gefitinib resistance, and inhibit PC9/GR cell growth in vitro and in vivo.